2019
DOI: 10.1002/dmrr.3129
|View full text |Cite
|
Sign up to set email alerts
|

The association between fasting plasma glucose and all‐cause and cause‐specific mortality by gender: The rural Chinese cohort study

Abstract: Background:To evaluate the association between fasting plasma glucose (FPG) and mortality by gender.Methods: A total of 17 248 eligible participants from a rural Chinese prospective cohort population were included. The same questionnaire interview and anthropometric and laboratory measurements were performed at both baseline (2007)(2008) and follow-up (2013-2014). Participants were classified according to baseline FPG and diabetic status by sex. Restricted cubic splines and Cox proportional-hazards regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Previous studies investigating associations between FG and the risk of all-cause mortality have reported J-shaped relationships, and our findings are in agreement with the cohort studies in earlier literature [4,23,24]. In our results, we noted this pattern in various categories of cause-specific mortality, in men and women, except in the case of cardiovascular deaths (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous studies investigating associations between FG and the risk of all-cause mortality have reported J-shaped relationships, and our findings are in agreement with the cohort studies in earlier literature [4,23,24]. In our results, we noted this pattern in various categories of cause-specific mortality, in men and women, except in the case of cardiovascular deaths (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…For this reason, fasting glucose (FG) is a useful indicator for screening and diagnosing diabetes mellitus. Additionally, it has recently been reported that an increased risk of mortality was associated with FG levels in a population-based study [4][5][6]. According to the literature, low https://doi.org/10.3904/kjim.2019.355…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, in most of the included studies, people with low blood glucose concentrations were not excluded. Some studies have shown that the association of fasting plasma glucose concentrations with cardiovascular disease has a J shaped curve 525354. The inclusion of people with low blood glucose concentrations in the reference group would make the association of prediabetes and risk towards null.…”
Section: Discussionmentioning
confidence: 99%